The Rising Working Poverty, Dependency Ratio and its Effect on Labour Productivity in Sub-Saharan Africa - Usman, Usman A.; Abubakar, Sadiq A. (ABUAD Journal of Social and Management Sciences, 2023)
This study seeks to analyse the effect of demographic patterns, dependency ratio, and population growth rate on labour productivity. The study employed the panel data set comprising seventeen (17) countries of Sub-Saharan Africa (SSA), spanning 2001 to 2022 and retrieved from World Development Indicators (WDI). The linear model approach and robust generalised least square technique were applied. Working poverty female aged 15 to 24 and male 15 to 24 reveal a positive and significant relationship with labour productivity. Similarly, working poverty female aged 25 and above, male 25 and above and dependency ratio exert a negative and significant effect on the outcome variable. Population growth also has a positive sign. Since members of both sex groups aged 15 to 24 are crucial to driving productivity levels, institutions need to focus on addressing social welfare and providing decent work and environment for these categories to improve productivity.